2008
DOI: 10.1007/s00534-007-1321-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of heparan sulfate on hepatocytes in regenerating rat liver

Abstract: These results suggested that this HS molecule, which contained about ten disaccharide units during proliferation, may be an initiator of hepatocyte proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Preparation of Hepatic Sulfated Glycosaminoglycans (sGAGs)-Hepatic sGAGs were isolated essentially as described previously (18,19) with some modification. Briefly, bovine liver was boiled and homogenized, and acetone precipitate was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of Hepatic Sulfated Glycosaminoglycans (sGAGs)-Hepatic sGAGs were isolated essentially as described previously (18,19) with some modification. Briefly, bovine liver was boiled and homogenized, and acetone precipitate was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Human hepatocellular carcinoma Huh7, HepG2, and Hep3B cell lines were cultured with DMEM, containing 10% FCS, antibiotics (100 U/mL penicillin and 100 U/mL streptomycin), and 2 mM glutamine, at 37 °C in a humidified atmosphere with 5% CO 2 . The rat hepatocytes were isolated through collagenase perfusion from 250-350 g Sprague-Dawley rats and cultured in 12-well plates in DMEM supplemented with 2% fetal bovine serum (FBS) with some modification (19). The culture medium was changed every 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…Using [35S] sulfuric acid incorporation, Otsu et al showed that, in the hepatic regeneration phase after hepatectomy, the synthesis of heparin sulfate proteoglycans, and to a lesser extent, of chondroitin/dermatan sulfate proteoglycans, increases up to 3-5 days and is temporally shifted compared to the stage of maximum mitosis that occurs 1-2 days following the surgical procedure [94]. However, Kimura et al have reported that heparan sulfate appears just hours after hepatectomy, suggesting a possible role of this GAG as an initiator of hepatocyte proliferation [95].…”
Section: Proteoglycans and Liver Regenerationmentioning
confidence: 99%